THE PLACE OF MUSICAL CULTURE AND UZBEKISTAN TRADITIONAL VALUES IN THE EDUCATION OF YOUTH. (Universal International Scientific Journal, 2026)
This article examines the relationship between musical culture and Uzbek traditional values ​​in the upbringing of young people. It examines the role of moral, aesthetic and social factors of such types of music as maqom, kuy-kashyk, ashulalar, folk songs in the formation of educational effects in the minds of young people. It shows that traditional values ​​​​(readiness to address, hospitality, appreciation of labor pride, and meetings, family and local harmony) are passed down from generation to generation through music, demonstrating examples of recent history and culture.
Keywords: folk, values, tradition, patriotic, education, maqom, melodies, folk songs, youth education, moral standards, national identity.